PENGARUH MANAGEMENT SKILL, FINANCIAL INVESTOR DAN HUMAN CAPITAL TERHADAP WOMEN ENTREPRENEURIAL SUCCESS - OEY HANNES WIDJAYA; RISWANTO RISWANTO; IAN NURPATRIA SURYAWAN (Jurnal Bisnis dan Akuntansi, 2014)
The purpose of this research is to investigation the factors that influence the women entrepreneurial success. With factors, management skills, financial investors and human capital. From the results, we get that management skill, financial investor and human capital have influence in the women entrepreneurial success.